Musharakah Mutanaqisah in Indonesia and Malaysia: Fatwa Institution, Regulation, and Recent Practice - Asyiqin, Istianah Zainal; Hamsin, Muhammad Khaeruddin; Anggriawan, Rizaldy; Fanani, Ahmad (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
Musharakah Mutanaqisah (MMQ) is one of Musyarakah's contract-based product developments. The application of MMQ as an Islamic banking financing product allows for the gradual purchase or commercial transfer of a portion of one partner's share to the other partner. The article aims to investigate the regulatory frameworks pertaining to MMQ in Indonesia and Malaysia. It also compares the associated institutions with the authority to issue regulations and policies surrounding the practice of MMQ. Furthermore, it analyzes and investigates a number of critical issues concerning the implementation of MMQ in both countries. This study is doctrinal legal research. It comprises the principle of law, legal systematics, synchronization of law, and legal history. The author also used statutory, conceptual, and comparative approaches. The result of the study shows that the regulatory framework in both countries was quite sufficient to accommodate the needs of MMQ customers and practitioners. Therefore, the study's novelty lies in its comprehensive comparative analysis of the regulatory frameworks and practices surrounding MMQ in Indonesia and Malaysia.